Efficient extraction of pectin from sisal waste by combined enzymatic and ultrasonic process. (June 2018) - Yang, Yishuo; Wang, Zhaomei; Hu, Die; Xiao, Kaijun; Wu, Jian-Yong
Abstract: Combined enzymatic and ultrasonic treatment was evaluated for efficient extraction of pectin from sisal waste in comparison with other extraction methods. The sequential treatment with enzyme (Celluclast 1.5 L) followed by ultrasound of sisal waste attained a much higher pectin yield of 31.1% than the ultrasound followed by enzyme, 14.6%. The pectin yield attained with the combined enzymatic/ultrasonic extraction was also higher than enzymatic extraction (9.4%), ultrasonic extraction (11.9%) and acidic extraction (5.8%). The pectin attained using the combined enzymatic/ultrasonic extraction (PEU) exhibited a higher galacturonic acid content (62.88%) and a higher degree of esterification (49.64%), indicating a better preserved polymer chain than that using acidic extraction (PA). PEU had a higher molar mass (7.65 × 10 5  g/mol) and a lower Mw /Mn than PA. Meanwhile, all sisal pectins showed the similar sugar composition regardless of the extraction methods according to FT-IR analysis. The results of rheological test showed that PEU in water turned from gel to liquid with increasing angle-frequency, while PA remained in a gel state. Compared with PA, the viscoelastic properties of PEU were more sensitive to temperature changes. SEM observation of the sisal residues after pectin extraction revealed a synergistic effect of the enzymatic and ultrasonic treatment on the solid structure, which may be contributable to the improved pectin extraction efficiency. The results from the present study suggest that the combination of enzymatic and ultrasonic extraction is an efficient process strategy for production of high quality pectins. Graphical abstract: Image 1 Highlights: Sisal waste is an attractive feedstock for pectin production. Combined enzymatic/ultrasonic extraction greatly promoted the sisal pectin yield. Sisal pectin from combined enzymatic/ultrasonic extraction exhibited high galacturonic acid content. The enzymatic and ultrasonic treatment has a synergistic effect on pectin extraction.